H4K20me1 and H3K27me3 are concurrently loaded onto the inactive X chromosome but dispensable for inducing gene silencing. (19th February 2021) - Tjalsma, Sjoerd J D; Hori, Mayako; Sato, Yuko; Bousard, Aurelie; Ohi, Akito; Raposo, Ana Cláudia; Roensch, Julia; Le Saux, Agnes; Nogami, Jumpei; Maehara, Kazumitsu; Kujirai, Tomoya; Handa, Tetsuya; et al.
Abstract: During X chromosome inactivation (XCI), in female placental mammals, gene silencing is initiated by the Xist long non‐coding RNA. Xist accumulation at the X leads to enrichment of specific chromatin marks, including PRC2‐dependent H3K27me3 and SETD8‐dependent H4K20me1. However, the dynamics of this process in relation to Xist RNA accumulation remains unknown as is the involvement of H4K20me1 in initiating gene silencing. To follow XCI dynamics in living cells, we developed a genetically encoded, H3K27me3‐specific intracellular antibody or H3K27me3‐mintbody. By combining live‐cell imaging of H3K27me3, H4K20me1, the X chromosome and Xist RNA, with ChIP‐seq analysis we uncover concurrent accumulation of both marks during XCI, albeit with distinct genomic distributions. Furthermore, using a Xist B and C repeat mutant, which still shows gene silencing on the X but not H3K27me3 deposition, we also find a complete lack of H4K20me1 enrichment. This demonstrates that H4K20me1 is dispensable for the initiation of gene silencing, although it may have a role in the chromatin compaction that characterises facultative heterochromatin. SYNOPSIS: H4K20me1 and H3K27me3 are concurrently loaded onto the inactive X chromosome, albeit with distinct genomic distributions. H4K20me1 enrichment is dispensable for the induction of X‐linked gene silencing. H4K20me1 and H3K27me3 concurrently accumulate at the inactive X chromosome. H4K20me1 enrichment depends on the B and C repeat regions of Xist RNA. Transcriptional silencing can be initiated in the absence of H4K20me1 accumulation at the inactive X. Abstract : H4K20me1 and H3K27me3 are concurrently loaded onto the inactive X chromosome, albeit with distinct genomic distributions. H4K20me1 enrichment is dispensable for the induction of X‐linked gene silencing.